A Comparative Study of Micellization Behavior of an Ethoxylated Alkylphenol in Aqueous Solutions of Glycine and Leucine. Issue 1 (23rd February 2013) - Chauhan, Suvarcha; Sharma, Kundan; Kumar, Kuldeep; Kumar, Girish
Abstract: Densities ( d ) and sound velocities ( v ) of an ethoxylated alkyl phenol surfactant in aqueous solutions of two amino acids, namely glycine and leucine, have been measured over a temperature range of 25–40 °C at intervals of 5 °C by using density and sound analyzers. Experimental data have been used to calculate the isentropic compressibilities ( κ s ), apparent molar volumes ( ϕ v ) and apparent molar adiabatic compressions ( ϕ κ ) in order to explain amino acid–surfactant interactions. The results have been discussed in terms of the effect of amino acids on the micellization behavior of the surfactant. A comparative study of both the amino acids has been carried out and is found that both amino acids produce a decrease in the CMC value of nonionic surfactant but to different extents.